Investigating Students’ Perception of Peer Assessment Practice in an EFL Academic Writing Class - Hoinbala, Festif Rudolf (Aisyah Journal of English Language Teaching (AIJELT), 2023)
Contrary findings have been revealed in the research on students' perspectives regarding peer assessment practice in the writing classroom. While several studies showed that peer assessment assisted students in identifying their strengths and shortcomings in writing skills, others considered this application to have a limited effect on students’ writing performance and encouraged little corrections. Nevertheless, some other research mentioned the fairness of this method towards the development of students’ composition. This recent study examines the perspectives of a group of university students in the English Education Study Program at Artha Wacana Christian University, who are mainly foreign language learners, on peer assessment in an English Academic Writing class. This study found that students’ perspectives regarding peer assessment are overall positive, and this practice improves the quality of their written work. However, in terms of interaction, the duration of time, and the application of peer assessment, some aspects reveal negative responses from the research subjects, which put a position on the neutral effect of this strategy. This study's findings are expected to reflect the participants’ responses on using peer assessment. It is also hoped that the findings from this study will be helpful for future research in designing a better peer assessment process and improving its implementation. Key words: Peer assessment, EFL classroom, Academic writing